Scientific Exegesis of Āyāt Kawniyyah in Tafsir Ulul Albab: A Reception-Theoretical Analysis of Agus Mustofa's Interpretation - Safitri, Fazida (QOF, 2026)
This article examines Agus Mustofa's reception of the verses on the universe in the Ulul Albab Juz 1 interpretation, highlighting his involvement in integrating Qur'anic interpretation with modern scientific perspectives through the lens of Roman Ingarden's reception theory. The focus of this study is on three issues: the shape of the earth, the structure of the sky, and the movement of the Sinai plate, which are interpreted to examine the relationship between the meaning of the text and the reader's knowledge. This research employs a library research method, using Agus Mustofa's works on Qur'anic interpretation and Roman Ingarden's writings as primary sources, while relevant scholarly literature serves as secondary sources. The findings indicate that Agus Mustofa applies a contextual approach to interpreting āyāt kawniyyah by incorporating contemporary scientific knowledge and technological developments into his interpretive framework. The factors influencing this approach include a social and educational background that encourages critical thinking, contemporary social dynamics that support interpretation with reference to science, and the influence of technological developments. This study contributes to the understanding of contemporary Qur'anic interpretation by illustrating how scientific knowledge may shape interpretive practices and by demonstrating the dynamic nature of Qur'anic interpretive methodology in modern contexts.